Undergraduate Nursing Students’ Experiences towards Clinical Placement in Intensive Care Units: A Literature Review - Lokuyaddage, S.; Medagedara, A.; Rathnayake, S. (My University, 2022)
Introduction: Clinical placement in the Intensive Care Unit (ICU) is a significant milestone in student nurses’ life as it is one of the specialized settings where critically ill patients are treated and cared for. Objective: To analyze the current evidence of the experiences of student nurses during their ICU placement. Methods: A systematic literature review was conducted following PRISMA guidelines. Two electronic databases (PubMed and Google Scholar) were consulted using keywords that include undergraduate nursing students, the ICU and experience. It featured articles published from January 2011 to July 2021. In data analysis, narrative synthesis was used. Results: The search generated 1784 publications. Following the screening process, seven articles based on qualitative studies from four countries were included. Four studies were from Turkey, and three studies were from South Korea, Spain and Saudi Arabia. Five meta-themes emerged: complex learning environment leads to stress and fear among students, dealing with critically ill patients and death is a stress full experience, communication in ICU is challenging, feeling incompetent in the provision of care, and selecting intensive care as a career choice. This review found that students were afraid of the complex environment of ICUs and were anxious and nervous when approaching patients with complicated diagnoses and different appearances. Difficulties in communicating with patients and staff have hindered effective care and led to psychological distress. Although students had negative experiences in ICU placements, they had opportunities for personal improvement, and most were interested in choosing intensive care nursing as a career choice. Conclusions: ICU clinical placement is a stressful experience for the majority of student nurses. However, they are interested to select ICU as a future career choice. These findings can be incorporated to design ICU course modules, revise curricula and plan ICU clinical placement effectively.
Keywords: Undergraduate; Nursing; Experiences; Clinical Placement; Intensive Care Unit